s=(12)gt2

Rewrite the equation as (12)gt2=s.

(12)gt2=s

Combine 12 and g.

g2t2=s

Combine g2 and t2.

gt22=s

gt22=s

Divide each term in gt22=s by 12t2.

gt22⋅112t2=s12t2

Simplify gt22⋅112t2.

Combine 12 and t2.

gt22⋅1t22=s12t2

Multiply the numerator by the reciprocal of the denominator.

gt22⋅(12t2)=s12t2

Multiply 2t2 by 1.

gt22⋅2t2=s12t2

Cancel the common factor of t2.

Factor t2 out of gt2.

t2g2⋅2t2=s12t2

Cancel the common factor.

t2g2⋅2t2=s12t2

Rewrite the expression.

g2⋅2=s12t2

g2⋅2=s12t2

Cancel the common factor of 2.

Cancel the common factor.

g2⋅2=s12t2

Rewrite the expression.

g=s12t2

g=s12t2

g=s12t2

Simplify s12t2.

Combine 12 and t2.

g=st22

Multiply the numerator by the reciprocal of the denominator.

g=s2t2

Combine s and 2t2.

g=s⋅2t2

Move 2 to the left of s.

g=2st2

g=2st2

g=2st2

Solve for g s=(1/2)gt^2